The association of vitamin D deficiency with non-alcoholic fatty liver disease - Metin Küçükazman; Naim Ata; Kür?at Dal; Abdullah Özgür Yeniova; Ay?e Kefeli; Sebahat Basyigit; Bora Aktas; Kadir Okhan Akin; Kadir A?ladio?lu; Öznur Sari Üre; Firdes Topal; Ya?ar Nazligül; et al. (Clinics, 2014)
OBJECTIVE: Vitamin D deficiency has been related to diabetes, hypertension, hyperlipidemia and peripheral vascular disease. In this study, we aimed to investigate the role of vitamin D status in non-alcoholic fatty liver disease. METHODS: We included 211 consecutive subjects to examine the presence of non-alcoholic fatty liver disease. Of these subjects, 57 did not have non-alcoholic fatty liver disease and 154 had non-alcoholic fatty liver disease. RESULTS: The non-alcoholic fatty liver disease group had significantly higher fasting blood glucose (p = 0.005), uric acid (p = 0.001), aspartate aminotransferase (p<0.001), alanine aminotransferase (p<0.001), γ-glutamyltransferase (p<0.0001), alkaline phosphatase (p = 0.028), HbA1c (p<0.001), ferritin (p<0.001), insulin (p = 0.016), C-peptide (p = 0.001), HOMA-IR (p = 0.003), total cholesterol (p = 0.001), triglyceride (p = 0.001) and white blood cell (p = 0.04) levels. In contrast, the non-alcoholic fatty liver disease group had significantly lower 25(OH)D levels (12.3±8.9 ng/dl, p<0.001) compared with those of the control group (20±13.6 ng/dl). CONCLUSIONS: In this study, we found lower serum 25(OH)D levels in patients with non-alcoholic fatty liver disease than in subjects without non-alcoholic fatty liver disease. To establish causality between vitamin D and non-alcoholic fatty liver disease, further interventional studies with a long-term follow-up are needed.